Diverse Voices of Disabled Sexualities in the Global South - Chappell, Paul.; de Beer, Marlene; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This volume aims to critically engage with constructs and experiences of disabled sexualities through Africa, Asia, Latin America and the Caribbean. In doing so, it is hoped that the questions raised, relfections, analyses and arguments will provide readers with a catalyst through which to (re)think disabled sexualities from the perspective of the Global South. What makes this edited volume unique is besides chapters from emerging academics and disability activists who either live or work in the Global South, it also includes personal contributions from disabled people across the Global South. This volume takes a broad perspective on disabled sexualities addressing such areas as gender, race, culture, colonialism, body image, sexual pleasure, sexuality education, sexual access, sexual and reproductive health services, queer sexualities, and sexual rights and justice. The volume will be of interest to international and national organisations for people with disabilities, gender and sexuality researchers, health professionals, social workers, academics and students at all higher education and training institutions interested in disability, gender queer and sexuality studies.
Chapter 1 Situating Disabled Sexual Voices in the Global South -- Section 1 Cultural Aesthetics of Disabled Sexual Lives and Bodies -- Chapter 2 Sexual Pleasure, Intimacy and Desire: The Mapping of My Brown Skin -- Chapter 3 Shooting Back and (Re)framing: Challenging Dominant Representations of the Physically Disabled Body in the South Africa -- Chapter 4 Fashioning Selves: Femininity, Sexuality and Disabled Women in India -- Chapter 5 Defining Me -- Chapter 6 Disability Porn: The Fetishisation and Liberation of Disabled Sex -- Section 2 Desiring Disability: Love, Relationships and Sexual Intimacy -- Chapter 7 How Disability "Killed" My Sexuality -- Chapter 8 Navigating Dating and Relationships with a Disability in Jamaica -- Chapter 9 Being Disabled, Black and Queer in South Africa: A Personal Journey -- Chapter 10 Candid Conversations: Narratives of Young Adults with Disabilities in Sri Lanka on Relationships -- Chapter 11 Experiences of Disabled Commercial Sex Workers in Zimbabwe -- Chapter 12 Informed Sexuality: The Influence of Lack of Information on the Sexuality, Relationships and Reproductive Health of Deaf Women in Addis Ababa -- Chapter 13 Disability Vagina Monologues Ethiopia -- Section 3 Sexual Access, Citizenship and Rights -- Chapter 14 Paternal Masturbation of Profoundly Disabled Son - South African Case Study -- Chapter 15 Surviving on the Margins of Society in China -- Chapter 16 Sexual Rights before and after the Convention on the Rights of Persons with Disability: A Colombian Experience -- Chapter 17 Sexuality Education for Learners with Disabilities: Views and Perspectives from Teachers and Child Care Providers in South Africa -- Chapter 18 Sexuality Education in Zimbabwe: Why Leave Disabled Girls and Disabled Women Behind? -- Chapter 19 When Sexuality Meets Disability: Experiences, Attitudes and Practices from China.
Keywords: Social medicine; Ethnology; Social service; Health, Medicine and Society; Sociocultural Anthropology; Social Work